2021
DOI: 10.1002/acr.24108
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Microvascular Dysfunction in Rheumatoid Arthritis Compared to Diabetes Mellitus and Association With All‐Cause Mortality

Abstract: Objective Coronary microvascular dysfunction (CMD) is a predictor of cardiac death in diabetes mellitus (DM) independent of traditional cardiovascular (CV) risk factors. Rheumatoid arthritis (RA) is a chronic inflammatory condition, with excess CV risk compared to the general population, in which CMD is hypothesized to play a role; however, there are limited data on CMD in RA and any association with clinical outcomes. The objective of this study was to compare the prevalence of CMD in RA to that in DM and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Recio‐Mayoral et al (70) also reported lower (impaired) MFR in RA and systemic lupus erythematosus patients versus controls ( P < 0.001) as demonstrated by cardiac PET‐CT, and MFR correlated inversely with disease activity (r = −0.65, P < 0.001). Microvascular dysfunction is a well‐documented complication of diabetes mellitus; Liao et al reported similar rates of impaired MFR in RA patients and diabetes mellitus patients (54% and 64%, respectively), and MFR <2 was significantly associated with all‐cause mortality (HR 2.43 [95% CI 1.40, 4.22]) (71). Amigues and colleagues (72) reported a mean MFR of <2.5 in 29% of RA patients without clinical CVD, and a mean MFR of <2.0 in 12%.…”
Section: Introductionmentioning
confidence: 99%
“…Recio‐Mayoral et al (70) also reported lower (impaired) MFR in RA and systemic lupus erythematosus patients versus controls ( P < 0.001) as demonstrated by cardiac PET‐CT, and MFR correlated inversely with disease activity (r = −0.65, P < 0.001). Microvascular dysfunction is a well‐documented complication of diabetes mellitus; Liao et al reported similar rates of impaired MFR in RA patients and diabetes mellitus patients (54% and 64%, respectively), and MFR <2 was significantly associated with all‐cause mortality (HR 2.43 [95% CI 1.40, 4.22]) (71). Amigues and colleagues (72) reported a mean MFR of <2.5 in 29% of RA patients without clinical CVD, and a mean MFR of <2.0 in 12%.…”
Section: Introductionmentioning
confidence: 99%
“…The TIMI frame count has been demonstrated to be useful in detecting coronary fl ow changes in patients with stent implantation [22] or impaired coronary microcirculation in patients who have impaired flow and increased burden of coronary atherosclerosis. [23] Previous observations have reported that females, [11,24,25] elderly patients, diabetes mellitus patients, [26,27] and patients with an elevated BMI [28] have been more likely to develop coronary microcirculation dysfunction. These reports are consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammatory conditions also pose greater risk of cardiovascular disease - patients with rheumatoid arthritis face a 1.5 fold higher risk than the general population [ 39 ]. One study looked at the incidence of decreased CFR, considered a surrogate for microvascular function among rheumatoid arthritis (RA) and diabetes mellitus (DM) patients.…”
Section: Clinical Presentation and Risk Factorsmentioning
confidence: 99%